Cybersickness in Head-Mounted Displays Is Caused by Differences in the User's Virtual and Physical Head Pose - Palmisano, Stephen; Allison, Robert S.; Kim, Juno (Frontiers in Virtual Reality, 2020)
Sensory conflict, eye-movement, and postural instability theories each have difficulty accounting for the motion sickness experienced during head-mounted display based virtual reality (HMD VR). In this paper we review the limitations of existing theories in explaining cybersickness and propose a practical alternative approach. We start by providing a clear operational definition of provocative motion stimulation during active HMD VR. In this situation, whenever the user makes a head movement, his/her virtual head will tend to trail its true position and orientation due to the display lag (or motion to photon latency). Importantly, these differences in virtual and physical head pose (DVP) will vary over time. Based on our own research findings, we propose that cybersickness in HMD VR is triggered by large magnitude, time-varying patterns of DVP. We then show how this hypothesis can be tested by: 1) systematically manipulating display lag magnitudes and head movement speeds across HMD VR conditions; and 2) comparing the user’s estimates of DVP and cybersickness produced in each of these conditions. We believe that this approach will allow researchers to precisely predict which situations will (and will not) be provocative for cybersickness in HMD VR..